Understanding and predicting flossing behavior in a rural Appalachian community using the multi-theory model - Rahib K. Islam; Manoj Sharma; Amanda H. Wilkerson; Bradford Layman; Clyde Dunn; Shamima A. Somi; Ratnesh Sharma; Karen Gruszynski; Syed S. Quadri; Vinayak K. Nahar; Robert E. Davis (Scientific Reports)
Abstract Effective flossing is essential for preventing periodontal disease. However, in a rural Appalachian community, adherence to flossing routines remains low, contributing to significant oral health disparities. The purpose of this study was to conceptualize intention of initiation and sustenance of flossing behaviors using the multi-theory model (MTM) of health behavior change. A cross-sectional survey was administered to individuals recruited from a shopping mall in rural Appalachia. The MTM constructs were measured and data were analyzed using multiple linear regression models. Of the 228 participants, 55% did not floss daily. Behavioral confidence (β = 0.571, p < 0.001) was a significant predictor for the intention of initiation of flossing among non-daily flossers, while emotional transformation (β = 0.377, p = 0.836) significantly explained sustenance among non-daily flossers. For daily flossers, changes in the physical environment (β = 0.432, p = 0.003) significantly predicted the intention of initiation of flossing, whereas emotional transformation (β = 0.344, p = 0.008) and practice for change (β = 0.594, p < 0.001) significantly predicted sustenance of flossing behavior. The MTM appears to be a robust framework for understanding and predicting flossing behaviors in rural Appalachian populations. Interventions designed to enhance behavioral confidence, physical environment changes, emotional transformation, and practice for change could improve flossing adherence. Further research should explore these constructs to develop targeted public health strategies.